QSO-galaxy correlations induced by weak lensing in arbitrary Friedmann-Lemaître cosmologies - Dolag, Klaus; Bartelmann, Matthias (Monthly notices of the Royal Astronomical Society, 1997)
We calculate the angular cross-correlation function between background QSOs and foreground galaxies induced by the weak lensing effect of large-scale structures. Results are given for arbitrary Friedmann-Lemaître cosmologies. The non-linear growth of density perturbations is included. Compared with the linear growth, the non-linear growth increases the correlation amplitude by about an order of magnitude in an Einstein-de Sitter universe, and by even more for lower Ω0. The dependence of the correlation amplitude on the cosmological parameters strongly depends on the normalization of the power spectrum.